The Effect of Entrepreneurship Education on Entrepreneurship Intention of Students of Private Islamic Universities in Jakarta - Hamidah; Bambang Eko Samiono; Ma’ruf Akbar (Journal of Business and Behavioural Entrepreneurship, 2018)
This study aims to analyze the effect of Entrepreneurship Education on Entrepreneurship Intention of students of private Islamic universities in Jakarta. This study shall be focused on the variables of entrepreneurial education, namely Attitude and Self Efficacy, to mediate the effect of entrepreneurship education on entrepreneurial intention. The object of the study was 400 students from private Islamic universities in Jakarta with accreditation A and B, entrepreneurial curriculum as faculty and university subjects, and entrepreneurial concentration in major. This study applied a multivariate analysis using Structural Equation Modeling (SEM) method. The findings suggest that Entrepreneurship Education does not have a positive direct effect on Entrepreneurial Intention, yet has a considerable effect on Entrepreneurial Self-Efficacy and Attitude. However, Entrepreneurial Self-Efficacy has no effect on entrepreneurial intention. Entrepreneurship Intention is influenced by Entrepreneurship Attitude. Furthermore, this study obtained a noteworthy finding, namely the effect of Entrepreneurial Self-Efficacy on Entrepreneurship Attitude.